Lifestyle and adherence to treatment of systemic arterial hypertension in elderly men - Falcão, Aline de Sousa (2018)
Objective: To assess the lifestyle and adherence to treatment of systemic arterial hypertension (SAH) in elderly men. Methods: This is a cross-sectional and descriptive study with a quantitative approach, developed with 254 elderly men, meeting the following inclusion criteria: male, aged over 60 years, undergoing follow-up of SAH evolution in primary care. Data collection took place by means of two questionnaires: a semi-structured one, containing questions related to personal and family data on health and lifestyle conditions, and the Questionnaire on Adherence to the Treatment of Systemic Arterial Hypertension, between October and December 2016. Results: A majority of the elderly men were aged between 70 and 79 years (93; 36.5%), marital status married/stable union (174; 68.5%) and retired (200; 78.7%). There was a predominance of hypertensive patients who stopped taking the antihypertensive medication at least once a year, and eat practically fat-free and sugar-free foods, without consumption of sugary drinks (120; 47.2%). Lifestyle is marked by the coexistence of food groups liable to improve or disturb the adherence to the treatment of hypertension in elderly subjects. Conclusion: Partial adherence was observed in the elderly men investigated, who adopt some healthy habits as a compensatory mechanism to maintain practices that hinder the adherence to treatment.